A probabilistic approach to delineating functional brain regions. - Kalbitzer,J; Svarer,C; Frokjaer,VG; Erritzoe,D; Baaré,WFC; Madsen,J; Hasselbalch,SG; Knudsen,GM (J Nucl Med Technol, 2009)
UNLABELLED: The purpose of this study was to develop a reliable observer-independent approach to delineating volumes of interest (VOIs) for functional brain regions that are not identifiable on structural MR images. The case is made for the raphé nuclei, a collection of nuclei situated in the brain stem known to be densely packed with serotonin transporters (5-hydroxytryptaminic [5-HTT] system). METHODS: A template set for the raphé nuclei, based on their high content of 5-HTT as visualized in parametric (11)C-labeled 3-amino-4-(2-dimethylaminomethyl-phenylsulfanyl)-benzonitrile PET images, was created for 10 healthy subjects. The templates were subsequently included in the region sets used in a previously published automatic MRI-based approach to create an observer- and activity-independent probabilistic VOI map. The probabilistic map approach was tested in a different group of 10 subjects and compared with a manual delineation approach. RESULTS: In addition to providing an observer-independent solution, the probabilistic map approach returned a higher specific binding determined in a larger region, ultimately providing better data fitting in kinetic modeling. CONCLUSION: We developed a fast, observer-independent, reliable approach to delineating regions that can be identified only by functional imaging, here exemplified by the raphé nuclei. This approach can be used in future studies to create functional VOI maps based on neuroreceptor fingerprints retrieved through in vivo brain imaging.